DAMPAK KEBIJAKAN PAUS FRANSISKUS DALAM NORMALISASI AMERIKA SERIKAT – KUBA 2013-2015 - Fifiria Noviyanti; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This reasearch explains about The Impact of Pope Francis’s Policy on normalization of the United States and Cuba. This research also describes of Pope Francis’s policy in the proccess of US-Cuba normalization. The diplomatic relations between US-Cuba have been frozen since US break off diplomatic relations with the Island Nation in 1961. The impact of this frozen relations has harmed people of the both sides, particularly the Cuban people who suffered from embargo of the United States. Pope Francis is the first pontiff of Latin America who played key role in the proccess of US-Cuba normalization.This reasearch theoretically has built with behavioralism perspective on International Relations and supported by individual behavior analysis, foreign policy and diplomacy theories. Data collection techniques using library research in the form of journals, books, official documents, articles and websites. Formulation of all arguments, facts, and theoretical framework on this reserach is guided by qualitative explanation methods. Scope of this research is about the impact of the Pope Francis’s policy on normalization of the United States and Cuba 2013-2015.This research also proves that Pope Francis’s policy affects to the relations of two countries untill normalization happened on December 17th, 2014. Pope started his step by writing forceful letters to Obama and Raul Castro, and then on October 2014, Vatican hosts the final negotiation between two delegations to reach the final agreement.Keywords: Pope Francis, Normalization, United States, Cuba